Associação de pais e mestres: atuação em uma escola de ensino médio - Lino, Luciana Marcela Baccarat Teixeira (2012)
This study begins with the following question: what are the characteristics and actions / contributions of a Parent-Teacher Association (PTA), considered active by the school community, to the institution which is part? The dissertation therefore pursued the overall objective of studying the characteristics and contributions of an active PTA considered by the school community to the institution which is part and the following specific objectives: 1) identify the characteristics of a PTA, under the law, and the real characteristics of PTA studied. Studying what the school creates in relation to the functions of the PTA, according to their local organization and culture. To analyze the relationship between the characteristics legal / formal PTA with a non-formal and informal characteristics, 2) identify the existence of contributions of PTA studied from the standpoints of formal and informal, financial, educational process of students and participation of parents and community to school. Identify which actions are performed by the PTA and how they occur. Studying what aspects that favor or hinder such actions, and 3) examine whether the PTA studied has traits of democratic performance. The PTA is one of the collegiate school and aims to: assist in the improvement of the educational process, assist the student and integrate family-school-community. To answer the original question and the general and specific objectives, this investigation worked with the theoretical references: Lima (2008), Canario (2005) and Apple (2001). From Lima were utilized the concepts of mode of operation diptych of the school as an organization and the perspective neotaylorista in school administration. From Canario the concepts that helped in the production of analyzes were: school totality, school as an organization and not as administrative unit and school as form, organization and institution. From Apple was used the concept of democratic school. As a methodological procedure I chose a documentary and empirical research with a qualitative approach which included the study of national and Sao Paulo laws and monitoring the practice of a PTA considered active for a public state school in Sao Paulo, located in the state capital. The research consisted of visits to the institution for observation of PTA meetings and interviews with parents and school managers, members of the collegiate. The initial hypotheses of this research, which could be confirmed during the study, are presented with the results of the PTA operates in accordance with the school community, working more for non-formal and informal rules, established under the organization's own specific school, more than by formal, and, lastly, that the contributions / actions of PTA studied to school at different intensities occurred in the financial, educational process and participation of parents and the community